The selective metabotropic glutamate receptor 5 antagonist mavoglurant (AFQ056) reduces the incidence of reflux episodes in dogs and patients with moderate to severe gastroesophageal reflux disease. Issue 8 (23rd March 2017) - Rouzade‐Dominguez, M.‐L.; Pezous, N.; David, O. J.; Tutuian, R.; Bruley des Varannes, S.; Tack, J.; Malfertheiner, P.; Allescher, H.‐D.; Ufer, M.; Rühl, A.
Abstract: Background: Transient lower esophageal sphincter relaxations (TLESRs) induced by gastric distension are modulated by the metabotropic glutamate receptor 5 (mGluR5) that influences the vagal reflex loop. We therefore aimed to examine the effects of the selective mGluR5 antagonist mavoglurant (AFQ056) on the number of TLESRs in dogs and reflux episodes in patients with gastroesophageal reflux disease (GERD). Methods: In a dog model, the number of meal‐induced TLESRs was determined after intravenous (0.03, 0.1, 0.3, and 1 mg kg −1 ) and oral (1, 3, and 10 mg kg −1 ) doses of mavoglurant with reference to vehicle. In a multicenter, randomized, double‐blind, placebo‐controlled, three‐period crossover study, the incidence of meal‐induced reflux episodes was assessed by esophageal impedance monitoring after single, oral doses of mavoglurant (50 and 400 mg) or baclofen (40 mg) in 30 patients with moderate to severe GERD. Key Results: In dogs, mavoglurant reduced the number of TLESRs after intravenous and oral administration. In patients with GERD, the incidence of postprandial reflux episodes was significantly lower at a dose of 400 mg mavoglurant (−37.5% ; 90% confidence interval [CI]: −57.8, −17.2), whereas there was no significant difference at 50 mg of mavoglurant compared to placebo. A significantly lower incidence of reflux episodes was also noted with the active comparator baclofen (−50.3%; 90% CI: −66.2, −34.3), thereby validating this study. Conclusions and Inferences: These data suggest a potential clinical benefit of mGluR5 antagonists such as mavoglurant in patients with GERD, particularly in those with persisting symptoms despite treatment with proton pump inhibitors. Abstract : Esophageal sphincter tone is partially modulated by metabotropic glutamate receptors. This study assessed the impact of the metabotropic glutamate receptor 5 antagonist mavoglurant (AFQ056) on gastro‐esophageal reflux in dogs and humans.